2015
DOI: 10.11646/phytotaxa.201.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Carpology of the genus Tragopogon L. (Asteraceae)

Abstract: Abstract67 species of Tragopogon were investigated with regard to fruit anatomy. The outer achenes, especially the beak and the central part of the seed-containing body, provide the most valuable features (diameter and outlines of the body and the beak, and arrangement of the mechanical elements in the body parenchyma). Some specimens of widely distributed taxa (e.g. T. capitatus, T. dubius, T. pratensis, T. pseudomajor) show variation in the character set and require more investigation prior to further taxono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Carpology corroborates the close affinity of S. rhodantha (SE Europe) to this clade and it has sometimes been considered as subspecies of S. purpurea (S. purpurea subsp. peristerica: Lack and Kilian in Strid and Tan 1991) or S. rosea (Greuter and van Raab-Straube 2006, sub Podospermum roseum subsp. peristericum).…”
Section: The Lineages Of the Scorzonera-pseudopodospermum-takhtajaniamentioning
confidence: 99%
“…Carpology corroborates the close affinity of S. rhodantha (SE Europe) to this clade and it has sometimes been considered as subspecies of S. purpurea (S. purpurea subsp. peristerica: Lack and Kilian in Strid and Tan 1991) or S. rosea (Greuter and van Raab-Straube 2006, sub Podospermum roseum subsp. peristericum).…”
Section: The Lineages Of the Scorzonera-pseudopodospermum-takhtajaniamentioning
confidence: 99%
“…abbreviatus according to the Flora of Turkey (Matthews, 1975). Further comparisons based on several morphological features that are important for the genus Tragopogon (Blanca and Diaz De La Guardia, 1997;Sukhorukov and Nilova, 2015) revealed that these samples distinctly differ from T. porrifolius subsp. longirostris (=T.…”
Section: Introductionmentioning
confidence: 99%
“…Members of this genus are known as Yemlik or Tekesakalı in Turkish (Güner et al, 2012) and consumed by local people as a source of food (Baytop, 2000). According to Borisova (1964), Blanca and Diaz De La Guardia (1997), and Sukhorukov and Nilova (2015), the members of the Tragopogon are almost impossible to be identified without mature achenes, phyllaries, and ligules colours. However, most of the Turkish taxa including T. porrifolius L. and T. longirostris Sch.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a limited number of surveys on the fruit‐coat micromorphology of the genus Tragopogon (Blanca and Díaz de la Guardia 1997, Sukhorukov and Nilova 2015). Sukhorukov and Nilova (2015) showed that the body of the achenes is often marked by tiny papillae or mamillae, outer epidermal cells vary in shape, forming stout multi‐layered conglomerations named tongue‐shaped ornamentation, especially in the rib area. The general achene characteristics of the new and related species are consistent with the view of Sukhorukov and Nilova (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Achene micrographs were generated by using JSM‐ 6510LV scanning electron microscope after coating with gold at Recep Tayyip Erdogan University. For the descriptive terminology of achenes, Barthlott (1981), Blanca and Díaz de la Guardia (1997) and Sukhorukov and Nilova (2015) were followed.…”
Section: Methodsmentioning
confidence: 99%